THE INFLUENCE OF THE INTERNET NETWORK ON YOUTH LIFESTYLE IN THE INFORMATION SOCIETY - J. SH. MUSTAFAYEV; ASADOV MADIYOR (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article discusses various changes in the minds of young people receiving modern education, their spiritual dependence, the impact of information attacks on young people, and the negative characteristics of popular culture.